Kimura disease in children: A report of 11 cases and review of the literature - Mai, Yumiao; Wang, Yingjie; Sun, Pan; Jing, Zhaohe; Dong, Pengpeng; Liu, Jian (Frontiers in Pediatrics, 2023)
Kimura disease (KD), also known as eosinophilic hyperplastic lymphoid granuloma, is a rare benign chronic inflammatory condition, characterized by the painless progressive mass located in the subcutaneous area of the head and neck region, elevated peripheral blood eosinophils and serum immunoglobulin E (IgE) levels. KD is rare in clinical practice with low incidence in children, so it is often misdiagnosis or missed diagnosis in pediatric patients.We retrospectively analyzed the clinical data of 11 pediatric patients with KD in order to provide more clinical information for the clinical features, diagnosis, and the treatment methods in children. There was a total of 11 pediatric patients with KD enrolled, including 9 male patients and 2 female patients (sex ratio 4.5:1). The median age at diagnosis was 14 years (range 5-18 years). The initial symptoms in all patients included painless subcutaneous masses and focal swelling. The duration of symptoms is from 1 month to 10 years, and the average time is 24.45 months. 6 patients had single lesions and 5 had multiple lesions. The highest proportion of lesion regions were parotid gland (n=5, 31.3%) and retroauricular (n=5, 31.3%), followed by neck (n=4, 25%) and others (n=2,12.5; elbow n=1; back n=1). The eosinophil absolute count elevated in all patients ranging from 0.71×109/L to 10.35 ×109/L (normal range 0.02-0.52×109/L). IgE levels were increased in all 7 patients who underwent serum immunoglobulin examination (normal range <100 IU/mL). Three patients received oral corticosteroid treatment while 2 cases relapsed. Three cases received surgical resection combined with oral corticosteroid treatment and no case relapsed. The other three patients received surgery and radiotherapy, surgery combined with corticosteroid and cyclosporin and corticosteroid combined with leflunomide, respectively, and no case relapsed. Our study shows that Kimura disease is rare and may has the atypical symptoms in pediatric patients, and combination therapy is recommended to reduce recurrence and long-term follow-up after treatment should be performed.